A new look at cytoskeletal NOS‐1 and β‐dystroglycan changes in developing muscle and brain in control and mdx dystrophic mice. Issue 12 (7th October 2013) - Janke, Alyssa; Upadhaya, Ritika; Snow, Wanda M.; Anderson, Judy E.
Background: Loss of dystrophin profoundly affects muscle function and cognition. Changes in the dystrophin‐glycoprotein complex (DGC) including disruption of nitric oxide synthase (NOS‐1) may result from loss of dystrophin or secondarily after muscle damage. Disruptions in NOS‐1 and beta‐dystroglycan (bDG) were examined in developing diaphragm, quadriceps, and two brain regions between control and mdx mice at embryonic day E18 and postnatal days P1, P10, and P28. Age‐dependent differential muscle loading allowed us to test the hypothesis that DGC changes are dependent on muscle use. Results: Muscle development, including loss of central nucleation and the localization of NOS‐1 and bDG, was earlier in diaphragm than quadriceps; these features were differentially disrupted in dystrophic muscles. The NOS‐1/bDG ratio, an index of DGC stability, was higher in dystrophic diaphragm (P10–P28) and quadriceps (P28) than controls. There were also distinct regional differences in NOS‐1 and bDG in brain tissues with age and strain. NOS‐1 increased with age in control forebrain and cerebellum, and in mdx cerebellum; NOS‐1 and bDG were higher in control than mdx mouse forebrain. Conclusions: Important developmental changes in structure and muscle DGC preceded the hallmarks of dystrophy, and are consistent with the impact of muscle‐specific differential loading during maturation. Developmental Dynamics 242:1369–1381, 2013. © 2013 Wiley Periodicals, Inc.